Integrating charge mobility, stability and stretchability within conjugated polymer films for stretchable multifunctional sensors - Sung Yun Son; Giwon Lee; Hongyu Wang; Stephanie Samson; Qingshan Wei; Yong Zhu; Wei You (Nature Communications, 2022)
Conjugated polymers are promising semiconductors for stretchable electronic devices but combining important properties such as high charge mobility, stability and stretchability remains challenging. Here, the authors demonstrate the synthesis of a thiophene based semiconducting polymer with cleavable side chains which shows significant improvement of charge mobility, stability and stretchability.